Translating Paralinguistic and Onomatopoeia: An Analysis on the Novel “Bumi Manusia” by Pramoedya Ananta Toer and its Translation ”This Earth of Mandkind” by Max Lane - Erna Wiles (Universitas Veteran Bangun Nusantara, 2021)
This article is a descriptive qualitative study that aims to describe the challenges and strategies in translating paralinguistic and onomatopoeias. Data were collected from a novel by Pramoedya Ananta Toer “Bumi Manusia” and its translation “This Earth of Mankind” by Max Lane. Content and discourse analyses were performed through reductions, codings, displays, and verifications. The analyses came to a conclusion that paralinguistic (and non- linguistic) as well as onomatopoeic features are culturally bound. Ones can exist in a language community but may not in another, and the adoptions can also differ; thus, the equivalence cannot be fully maintained. Analyses on